Petiole N, P, K Concentrations and Yield of the Potato Cultivar Molli from Certified Organic Amendments and Fertilizer Formulations. Issue 10 (30th May 2016) - Collins, H.P.; Porter, L.; Boydston, R.A.; Alva, A.; Cordoba, B. Chaves
ABSTRACT: This study evaluated the petiole uptake of nitrogen, phosphorus, potassium, and sulfur (N, P, K, and S) by the potato from two seed meals, mint compost, and five commercially available organic fertilizers under an irrigated certified organic production system. Available soil nitrate (NO3 -N) and ammonium (NH4 -N) from each amendment averaged 115 kg N ha −1 at application and 25 kg N ha −1 30 d after planting through harvest, with minor differences between fertilizers. Petiole N declined from an average of 25, 000 mg N kg −1, 4 wk after emergence to 3, 000 mg N kg −1 prior to harvest. Petiole P and K concentrations were maintained above 4, 000 mg P kg −1, 10, 000 mg K kg −1, and 2, 000 mg S kg −1 tissue, respectively, throughout the growing season in all treatments. Tuber yields were not different between fertilized treatments averaging 53 Mg ha −1 . This study provides organic potato growers baseline information on the performance of a diverse array of organic fertilizers and amendments.